Enhancing Mathematical Critical Thinking Skills through the Integration of Ethnomathematics, Augmented Reality, Artificial Intelligence, and Deep Learning: A Mixed-Methods Study - Heru Kurniawan; Nila Kurniasih; Muhammad Hamid Jumasa; Marzia Khatan Smita (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Critical thinking skills remain an urgent necessity in mathematics education, particularly in 21st-century learning contexts. Conventional teaching practices have proven insufficient in promoting these skills, requiring innovative approaches that integrate technology and culture. This study examines the effectiveness and practicality of mathematics learning integrating Ethnomathematics, Augmented Reality (AR), Artificial Intelligence (AI), and Deep Learning (DL).Employing a mixed-method design with sequential explanatory approach, the research involved junior high school students in Purworejo, Indonesia. The quantitative phase applied a quasi-experimental one-group pretest-posttest design to measure critical thinking improvement, while the qualitative phase explored teachers' and students' perceptions through interviews, observations, and response questionnaires. Quantitative results showed a significant increase in students' critical thinking ability (t = 4.126, p < 0.05) with an N-Gain score of 73%, categorized as high. Qualitative findings revealed positive responses: teachers considered the model innovative, feasible, and aligned with curriculum goals, while students reported higher engagement, clearer understanding of abstract concepts, and stronger motivation to learn mathematics. The integration proved most effective in enhancing interpretation and evaluation skills among critical thinking components. The integration of Ethnomathematics, AR, AI, and DL proved both effective and practical in fostering critical thinking. These findings demonstrate the potential of culture-based learning combined with advanced technological support to prepare students for future challenges.